(untitled) (Journal Intellectual Sufism Research (JISR), 2023)
This research is classroom action research with two ( II) cycles which aims to determine the improvement in learning outcomes and responses of class IX-B students at SMP Negeri 21 Surabaya in learning the material. Agreement and Disagreement through models Small Group Discussio n . Data collection methods include observation, questionnaires and tests . Subject study is participant educate class IX-B SMPN 21 Surabaya Academic Year 2023/2024. Object study is enhancement results learn and respond students on the material Agreement and Disagreement through models Small Group Discussion. Research result showing that in cycle I the percentage completeness Study student reached 64% and rising to 88% in cycle II. Response student to application method Small Group Discussion showing positive response . _ Therefore can concluded that application method small group discussions can increase learning outcomes and student responses _ significant to the eye Middle School English lessons This research is classroom action research with two ( II) cycles which aims to determine the improvement in learning outcomes and responses of class IX-B students at SMP Negeri 21 Surabaya in learning the material. Agreement and Disagreement through models Small Group Discussio n . Data collection methods include observation, questionnaires and tests . Subject study is participant educate class IX-B SMPN 21 Surabaya Academic Year 2023/2024. Object study is enhancement results learn and respond students on the material Agreement and Disagreement through models Small Group Discussion. Research result showing that in cycle I the percentage completeness Study student reached 64% and rising to 88% in cycle II. Response student to application method Small Group Discussion showing positive response . Therefore can concluded that application method small group discussions can increase learning outcomes and student responses significant to the eye Middle School English lessons